IMPLEMENTASI METODE AT-TARTIL DALAM MENGATASI KESULITAN MEMBACA AL-QUR’AN PESERTA DIDIK SMP NU SUNAN GIRI KEPANJEN - Alif Achadah, Iftitah Maghfiroh (JIPI (Jurnal Ilmiah Pendidikan Islam), 2023)
The most important element in teaching and learning activities is the learning method, considering that one method of learning to read the Qur'an is practical, effective, efficient and fast in understanding the learning of the Qur'an which leads students to be able to develop reading the Qur'an, namely At-Tartil method. The At-Tartil method is a method of learning to read the Qur'an in accordance with grammatical rules and packaged in a concise and pleasant form. This research is motivated by the lack of awareness of students in participating in learning the Qur'an and the ability to read the Koran of students at the junior high school level, which is considered quite low. The purpose of this research is to find out the extent to which the At-Tartil method overcomes students' difficulties in reading the Qur'an. This research uses a descriptive qualitative apporach. The results showed that: (1). The results of the application of the AtTartil method in general are: (a). Increasing the ability to read the Qur'an of students. (b). Can read the Qur'an according to the rules of Tajweed law. (c). Increased ability to memorize short letters and reading prayers of students. (2). There are several obstacles in the application of the At-Tartil method, namely: (a). Lack of mastery of delivering material for some teachers. (b). Lack of awareness of students to enter class on time.